Neuroarchitecture applied to the study of psychological conditions within physical rehabilitation spaces - Pazmiño, Maria Fernanda; Pérez Mato, Daisy de la Caridad; Flores Beltrán, Patricia Katherine; Castro, Rosanna Elizabeth Rivera; Martínez, María Gabriela Chica (Eximia, 2023)
Neuroarchitecture as a multidisciplinary study science has been influenced in Ecuador at the case study level to buildings without spaces for external interaction with nature or internal spatial development, which has caused poor treatment. The objective of this scientific article is the design of neuroarchitecture parameters applied to architectural and spatial design to improve treatment in rehabilitation spaces. The considerations will be evaluated under a quantitative approach methodology of the architectural spaces and the user’s perception through the decision-making scheme of the Kepner and Tregoe Method that analyzed the situation, evaluated results and established potential risks within the study. In conclusion, the characterization of the architectural spaces by shape and color contributed to the perception of tranquility within the space, the contact with the green areas improved the cognitive and sensory conditions of the users, integrating better with their environment, while the design of the Semi-open spaces and open spaces generate greater confidence and tranquility for comprehensive socialization, so it can be determined that the neuroarchitecture focused on the conditional evaluation and decision-making of the user improves the satisfactory treatment of patients by 90%.